2006
DOI: 10.2307/20445337
|View full text |Cite
|
Sign up to set email alerts
|

Associative and Phonological Priming Effects after Letter Search on the Prime

Abstract: Responses to target words typically are faster and more accurate after associatively related primes (e.g., "orange-juice") than after unrelated primes (e.g., "gluejuice"). This priming effect has been used as an index of semantic activation, and its elimination often is cited as evidence against semantic access. When participants are asked to perform a letter search on the prime, associative priming typically is eliminated, but repetition and morphological priming remain. It is possible that priming survives l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
1

Year Published

2006
2006
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 50 publications
(40 reference statements)
3
10
1
Order By: Relevance
“…However, like , we used a short SOA with a delayed dual-response procedure (Friedrich, 1993) in which participants withheld the prime response until after the target response had been made. Thus, the attenuation and elimination of semantic priming that were observed by and in our study cannot adequately be explained by the blockage of a retrospective process of the sort that was suggested by Kahan et al (2006).…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…However, like , we used a short SOA with a delayed dual-response procedure (Friedrich, 1993) in which participants withheld the prime response until after the target response had been made. Thus, the attenuation and elimination of semantic priming that were observed by and in our study cannot adequately be explained by the blockage of a retrospective process of the sort that was suggested by Kahan et al (2006).…”
Section: Discussioncontrasting
confidence: 42%
“…Nevertheless, it is not clear that the N400 pattern observed in their study reflects fast-acting semantic activation, because the SOA in their experiment was approximately 2 sec long. Kahan, Sellinger, and Broman-Fulks (2006) suggested that the elimination of priming by letter search on the prime reflects the blockage of a retrospective process akin to involuntary aware memory (see, e.g., Kinoshita, 2001;Mace, 2003aMace, , 2003b instead of the blockage of spreading activation. They base this idea on the fact that the SOA between the prime and target is long in letter search experiments in comparison with typical semantic priming experiments (e.g., Neely, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this possibility, presentation of the color word at the cued location after a 100-msec SOA produced a Stroop effect of 68 msec in Brown et al's (2002) study, as compared with 26 and 27 msec, respectively, in the present Experiments 1 and 2. This difference could reflect stronger activation of vocal naming responses than of keypress responses by either semantic or phonological codes (Kahan, Sellinger, & Broman-Fulks, 2006). Despite the large difference in size of baseline Stroop effects, the reduction when the color word occurred at the unattended location was of similar magnitude in Brown et al's (2002) study and ours.…”
Section: Ior Trialssupporting
confidence: 44%
“…As is typically found in the literature, LS on the prime eliminated both Sem priming (see Tse & Neely, 2007, for a review) and O/P priming (Ferguson & Besner, 2006;Kahan et al, 2006) for RTs. Although Tse and Neely observed LS Sem priming for targets with word frequencies comparably low to those of the present targets, we conjecture that we did not obtain LS Sem priming here because the prime-target association strengths and semantic overlap were too low to produce a detectable LS Sem priming effect even with our low-frequency targets.…”
Section: Discussionmentioning
confidence: 58%
“…Although our targets were low in frequency, which could lead to non-null LS semantic priming (Tse & Neely, 2007), the weaker association strengths and lower semantic relatedness values of our pairs may yield a semantic priming effect that still cannot be detected for semantically related prime-target pairs that are not also O/P related. If that were so, our materials would still allow us to test whether semantic activation from an LS prime that is too weak to be detected by itself could be detectable when summated with a null LS O/P priming effect (Ferguson & Besner, 2006;Kahan et al, 2006).…”
Section: Materials and Designmentioning
confidence: 99%